The redevelopment of the Kay picture test of visual acuity - Ashli Milling; David Newsham; Laurence Tidbury; Anna R. O'Connor; Hazel Kay (British and Irish Orthoptic Journal, 2015)
Aims:  To validate the design of updated optotypes to be used in the Kay picture acuity tests to improve the resolution acuity, recognition, repeatability and comparisons with gold standard logMAR acuity assessments. Methods: The study was completed in four phases. Inball phases the pictures were presented on a monitor as a single crowded optotype, with five optotypes at each visual acuity (VA) level. Phase one assessed the resolution acuity for 25 pictures, eight Landolt Csband five ETDRS letters. The recognition phase (phasebtwo) assessed children (18 months to 5 years) to determine which pictures were most commonly identified. During phase three, the resolution acuity of a reduced number of pictures and the Landolt C were reassessed to ensure that fatigue had not influenced the initial results. Phase four compared the new Kay pictures with LEA symbols and the ETDRS (part a), and repeatability of the Kay pictures and the ETDRS chart (part b). Results:  'Phase one (resolution acuity)': 50 adult subjects were tested. The mean (±SD) acuity scores achieved using each of the 25 pictures ranged from -0.123  ±0.124 to -0.308  ±0.105. The mean (±SD)bacuity for the eight Landolt C orientations was -0.059   ±0.120, and -0.128  ±0.101 for the ETDRS letters. Following this analysis, three pictures were removed. Phase two (Recognition): 420 children were assessed (54% male) using the remaining 22 pictures. Analysis resulted in the removal of 10 pictures based on the recognition levels. Phase three (resolution acuity): 43 adult subjects were tested with the remaining 12 pictures. The picture selection was reduced to six based on a combination of similar mean bias levels, recognition levels in all children and recognition levels in the youngest children. Phase four (a) (comparability): 113 adult subjects were tested. The mean bias indicated similar results between the tests. The limits of agreement for ETDRS versus Lea symbols were slightly wider than for ETDRS versus Kay pictures. Phase four (b) (repeatability): 100 adult subjects were tested. Paired 't'-test analysis demonstrated no significant difference between tests in either ETDRS ( p = 0.1) or Kay pictures ( p = 0.1). Mean bias for both tests was 0.01 logMAR with similar limits of agreement. Conclusion:  The newly designed Kay picture optotypes have been shown to be reliably recognised by a paediatric population. In a six-picture test format the newly designed optotypes with single picture presentation and crowding bars have been shown to be a reliable and repeatable VA test in an adult population with good agreement with current gold standard VA assessment methods. Normative data in a paediatric population are now required.